Mendesain Perdamaian Di Tengah Konflik: Imajinasi dan Strategi - Rahmat, Paul (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2006)
Global peace is an actual issue that is almost relevant to every corner of the world. While conflicts for any reason seem to be unavoidable, many people understand that there are many innocent victims. Many of these victims in fact have nothing to do with the core of the conflict, however, they suffer a lot. Therefore, some significant and crucial steps should be taken in order to promote peace. Using a case of woman movent in Wajir, Kenya, the author proposes that the first step is to realise that there are moral values that could serve as inner power to promote peace. Further steps should be strategically planned according to certain context, such as